Mountains of the intertropical passive margins and their cartographic representation: methodological proposal in different litostructural arrangements: methodological proposal in different structural arrangements - Neto, Roberto Marques (Revista Brasileira de Geomorfologia, 2025)
The core hypothesis of this article considers that methodological approaches related to geomorphological cartography must seek standardization based on landscape types. Thus, a methodological proposal for geomorphological cartography in mountainous landscapes is presented, with demonstrations in compartments structured in three distinct lithostructural bases located in the context of Serra da Mantiqueira: nepheline-syenites, gneiss-granites and quartzites. The results showed a similar geomorphological organization for the different compartments, admitting the same methodological approach and the adoption of a unified legend, since the geomorphic facts found were convergent, despite the differences in the geological bases between the areas. It is postulated that the methodological approach presented can be applied to different geomorphological contexts located in the large escarpments of the intertropical passive margins, thus making the universalization of interpretative and technical procedures compatible with the also universal character of this landscapes.